Classroom Management based on Ergonomic Aspects in Supporting Learning in Elementary Schools - Titisari, Alifah Dian; Kaltsum, Honest Ummi (Universitas Muhammadiyah Surakarta, 2023)
Purpose: Managing the classroom is one of the teacher's efforts in organising and designing the classroom to create a conducive learning environment. The objectives of this research are as follows: (1) To determine the implementation of classroom management by paying attention to ergonomic aspects in elementary schools; (2)Assessing teachers' understanding of classroom management based on ergonomic principles in learning; (3)Knowing the obstacles faced by teachers and students in managing classrooms to support learning. Methodology: This research uses qualitative methods through a case study. The data collection techniques used were interviews, observation, and documentation. This research was carried out in Third-Grades of Muhammadiyah PK Baturan Elementary School. The data analysis used is thematic analysis, which involves reading through a set of data and looking for patterns of meaning in the data to find themes. Results: The research results show that: (1) Classroom management is a supporting factor in creating conducive and effective learning. There needs to be special attention paid to ergonomic aspects consisting of lighting, thermal conditions, student seating arrangements, and noise. (2) Teachers need to increase their knowledge and understanding of the role of ergonomics in learning. This can be seen from the teacher's role in managing the class and students so as to create an ideal learning climate. (3) Obstacles in managing classes based on ergonomic principles in learning are felt by teachers and students to hinder their teaching and learning activities. Applications/Originality/Value: This research reveals that educators need to understand ergonomic classroom management in supporting learning in order to achieve learning objectives.